1996
DOI: 10.1126/science.273.5281.1555
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Determinants of Species Loss in Remnant Prairies

Abstract: Recensuses of 54 Wisconsin prairie remnants showed that 8 to 60 percent of the original plant species were lost from individual remnants over a 32- to 52-year period. The pattern of species loss was consistent with the proposed effects of fire suppression caused by landscape fragmentation. Short, small-seeded, or nitrogen-fixing plants showed the heaviest losses, as did species growing in the wettest, most productive environments. The interruption of landscape-scale processes (such as wildfire) by fragmentatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
318
3

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 431 publications
(341 citation statements)
references
References 29 publications
20
318
3
Order By: Relevance
“…Supporting the hypotheses and consistent with other studies (Leach and Givnish 1996;Towne and Knapp 1996), legume cover increased with fire frequency. However, the magnitude of this change was small, occurring only in a few plots in the annually burned treatment and only after more than 10 years of burning.…”
Section: Discussionsupporting
confidence: 81%
“…Supporting the hypotheses and consistent with other studies (Leach and Givnish 1996;Towne and Knapp 1996), legume cover increased with fire frequency. However, the magnitude of this change was small, occurring only in a few plots in the annually burned treatment and only after more than 10 years of burning.…”
Section: Discussionsupporting
confidence: 81%
“…For example, the Biological Dynamics of Forest Fragments Project of Manaus, Brazil finds that relatively unimportant drivers in intact systems can come to dominate fragmented systems. Examples include increased wind shear in tropical forest fragments (Laurance et al 2011), and reduced fire frequency, in prairie systems (Leach and Givnish 1996). We need further work on altered disturbance Landscape Ecol (2016) 31:219-227 221 regimes, especially focusing on the integration of patch shape and matrix characteristics, to generalize these results across landscapes and disturbance regimes.…”
Section: How Does Fragmentation Predictably and Consistently Alter Thmentioning
confidence: 99%
“…Grassland plants have shown genetic changes as a result of management in as little as 60 years (Painter and others 1989). Many species in remnant prairies have become extinct within the last 60 years probably due to fragmentation and certain management practices; more species probably became extinct prior to this (Leach and Givnish 1996). Gibson (1988) observed that even after several years of identical treatment two areas may still have different plant communities, probably a result of past land use.…”
Section: Prairiementioning
confidence: 99%